Embedded design consideration for the implementation of food intake monitoring system:validated using LabVIEW software - Mahesh, C; Kingston Stanley, P; Vijaydaniel, P; Saneevi Gandhi, A (International Journal of Engineering and Technology, 2018)
Memory loss is a common problem found among old people, the person may forget mealtime altogether due to memory loss. This paper proposes an idea for a monitoring system which will monitor the old people food intake from a remote place and generate an alarm locally. A wearable system is designed usingpiezoelectric sensor that will sense the trachea movement during food ingestion and produces an output signal with variations in the frequencies over time. Based on the detected frequency, food type is classified. Food classification algorithm is depends on Time-Frequency analysis of the piezoelectric output and the wearable design transmits the signals to PC via Bluetooth module. The received signal is processed by LabVIEW and accuracy is tested.